Modern contraceptives utilization and associated factors among married women of reproductive age in Holeta town, central Ethiopia - Ephrem Yohannes Roga; Gemechu Gelan Bekele; Berhanu Ejara Moti; Dajane Negesse Gonfa; Amare Tesfaye Yami; Meseret Robi Tura (Elsevier, 2023)
Background: Modern contraceptives have been identified as key strategies to control fertility and improve maternal health. However, it was poorly utilized in Ethiopia. Hence, this study aimed to assess modern contraceptive utilization and associated factors among married women of reproductive age groups in Holeta town, central Ethiopia, 2021. Methods: A community-based, cross-sectional study was conducted from January 01-30, 2021, among 343 women of reproductive age in Holeta town. Pretested structured questionnaires were used to collect data. Both bivariate and a multivariable logistic regression model was used, and statistical significance was determined with a 95% confidence level and a P value of less than 0.05. Result: The overall magnitude of modern contraceptive utilization was 52.5%. The desire for more children [AOR = 0.52, 95% CI: (0.26-0.89)], a history of child death [AOR = 1.54, 95% CI:(1.22-3.01)], religious prohibition [AOR = 0.37, 95% CI (1.01-3.84)], inter-spousal discussion [AOR = 5.95, 95% (1.31-7.01), and history of unintended pregnancy [AOR = 1.71, 95% CI (1.01-2.60)] were significantly associated with the use of modern contraceptive methods. Conclusion and recommendation: In comparison to national goals set to be reached by 2024/25, the rate of current modern contraceptive use is determined to be good. Therefore, program implementers need to address these significant factors and encourage couples to discuss issues related to reproductive health, including family planning.